A long‐term study of burning effects on a plant pathogen in tallgrass prairie. (5th March 2017) - Dendy, S. P.; Tong, B.; Alexander, H. M.; Fay, P. A.; Murray, L.; Xing, Y.; Garrett, K. A.
Abstract : Tallgrass prairie species have evolved with regular exposure to fire. However, burning has been used as a management tool for reducing plant disease in agricultural systems, posing the question of how plant pathogens of tallgrass prairie would be affected by burning. The rust fungus Puccinia dioicae, infecting Erigeron strigosus (Asteraceae), was studied for 8 years in long‐term experiments to evaluate the effects of burning in native tallgrass prairie. This experiment also allowed evaluation of the effects of nutrient additions, although E. strigosus was rare in the plots with added nutrients in most years. Burning reduced rust severity in most years, but effects from additions of nutrients were rarely observed. There was high interannual variation in rust severity within a location, suggesting that weather may be the most important of these three abiotic factors in determining infection. An analysis of weather variables associated with disease severity found that solar radiation in the month prior to sampling was associated with severity in unburned plots; temperature approximately 2 months prior to sampling was also associated with severity in burned plots. High interannual variation also suggests that the effects of this pathogen on its host would be sporadic and difficult to study in short‐term experiments.